2013
DOI: 10.3846/16111699.2012.701229
|View full text |Cite|
|
Sign up to set email alerts
|

Post-Event Visits as the Sources of Marketing Strategy Sustainability: A Conceptual Model Approach

Abstract: Abstract. While extant literature has mainly concentrated on contemporaneous event tourism marketing (i.e., on visiting the city during or around the event) and on intentions to revisit after the event's completion, this research investigates the impact of the event on the decisions of potential tourists/visitors who have never visited the host city and want to visit it after the event's completion. Research in this area, especially in those emerging markets where event marketing is developing rapidly, is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 78 publications
2
25
0
Order By: Relevance
“…We considered the occurrence of a unique OTU in any single sample as a prey item, which in total amounted to 604 prey items (assigned to 143 OTUs) of which 61% were assigned to species level (Figure 2a). Eight samples contained DNA from a host-specific ectoparasite of P. kuhlii, namely, the bat bug Cacodmus vicinus (Quetglas, Balvín, Lučan, & Benda, 2012), which was probably consumed while grooming, further validating the sample source.…”
Section: Re Sultsmentioning
confidence: 89%
“…We considered the occurrence of a unique OTU in any single sample as a prey item, which in total amounted to 604 prey items (assigned to 143 OTUs) of which 61% were assigned to species level (Figure 2a). Eight samples contained DNA from a host-specific ectoparasite of P. kuhlii, namely, the bat bug Cacodmus vicinus (Quetglas, Balvín, Lučan, & Benda, 2012), which was probably consumed while grooming, further validating the sample source.…”
Section: Re Sultsmentioning
confidence: 89%
“…The case study based on the 2014 Shanghai stampede tragedy revealed why it happened, in what way in affected local citizens, and for how long. Compared with traditional sociological methods, the proposed approach combines the methods of social sensing, machine learning, and natural language processing and can thus facilitate efficient data acquisition and analysis [6][7][8][9][10][11][12][13][14][15][16][17]. Compared with some of the existing social network-based public opinion mining, this paper considers the dimensions of time and geo-space in observing the impact of social events in addition to sentiment analysis and opinion mining [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the tourism aspect, Breitsohl and Garrod used an online survey to examine people's cognitive reactions to an incident of unethical behavior at a tourist destination [16]. By means of questionnaires, Li et al studied the public preferences for a post-event visit to the host city [17]. In recent years, the research potential of multi-sourcing social data has gradually attracted the attention of scholars.…”
Section: Traditional Research On the Impact Of Social Eventsmentioning
confidence: 99%
“…The presentation of FSE image will have a positive impact on people's perceptions. This will in turn affect their attitudes regarding FSE activities (Weigelt & Camerer, 1988;Pearce, 1997;Li, Song, & Collins, 2014). Using the SET cost-benefit framework, residents evaluate FSE activities via a social exchange.…”
Section: Evaluation Of Fse Image Residents' Perceived Value and Attimentioning
confidence: 99%